Soil Erosion Dust Control and Sand Stabilization - Katra, Itzhak (MDPI - Multidisciplinary Digital Publishing Institute, 2021)
Soil erosion by wind is significant to Earth systems and human health. There is a strong interest in understanding the factors and processes of soil erosion by wind as well as in developing and applying methods to control dust emission from soils and to stabilize active sands. The Special Issue contains information on applications of natural and synthetic materials to reduce soil erosion, development of materials and methods, experimental methods and modeling, impacts on the soil quality and the environments, and quantification of the efficiency in dust control and sand stabilization applications.